Partisipasi Kaum Muda Dalam Pendalaman Iman Di Lingkungan St. Yakobus, Paroki MDKS - Patrisia Rera Bato; Intansakti Pius X (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Catholic young people (KMK) or commonly called Catholic Young People (OMK) are the next generation of the nation, especially in the Catholic Church, these young people play a very important role. In the Catholic Church, young people participate more. The problem here is that young people's participation in deepening their faith in this environment is very lacking. From the formulation of this problem, the aim of this analysis is to understand the extent of participation of the young Catholic generation in deepening their faith in the MDKS Parish environment, using qualitative methods involving interviews with parents of the young generation at St. James. This research also involves literature analysis which includes books, journals and articles relevant to the research title to be discussed. Findings from interviews with key informants show that the lack of young people's participation in this matter is often caused by the large number of school or college assignments that have to be done, as well as by the influence of sophisticated technology. This phenomenon shows that young people tend to be fixated on their own digital world, which sometimes makes them forget their responsibilities as members of Catholic Young People (OMK) or young Catholics. The conclusions of this research illustrate the complexity of the challenges and opportunities faced by young Catholics in their participation in deepening their faith in the St. James, MDKS Parish.